iNEMO : “Health enhancement" – B - Nguyen, Duy Anh. (2013)
Health Enhancement has been more and more noticed in both the scientific world and Healthcare. As the number of people sustained obesity has been nearly double since 1980 , we - human - have put ourselves on much higher risks of critical diseases and deaths. However, obesity and overweight are totally preventable through regular physical exercises and healthy, nutritious food choices.